Pediatric Cancers - Agarwal, Saurabh; Yang, Jianhua (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Childhood cancer or pediatric cancer is one of the leading causes of death among children. Treatment strategies for pediatric cancers include chemotherapy, surgery, radiation, and stem cell transplantation. These therapeutic regimens are well known to develop highly toxic and long-lasting side-effects including secondary cancers in the future lifespan of pediatric patients. Despite these intensive therapeutic regimens, cancer may still relapse as refractory and metastatic cancer. Therefore, further understanding the causes of different pediatric cancers, mechanisms of drug-resistance, and causes of relapse and metastasis is required for developing and advancing less toxic and more effective therapeutic strategies for pediatric cancers. Recent advancements in immunotherapies and targeted therapeutic approaches using pharmacological inhibitors are one step in this direction.In this Special Issue of Cancers, authors contributed original research and review articles focusing on different aspects of pediatric cancer development, causes, maintenance, and therapeutic strategies. The collected articles in this Special Issue will further enhance our knowledge and understanding of pediatric cancers and drive the development of novel therapeutic strategies.